Зміни лабораторних показників та функціонального стану лівого шлуночка у чоловіків з надлишковою масою тіла та ожирінням залежно від важкості хронічної серцевої недостатності - Бідзіля, Петро Петрович; Бидзиля, П. П. (My University, 2016)
Досліджено зімни лабораторних показників та функціонального стану лівого шлуночка (ЛШ) у чоловіків з надлишковою масою тіла та ожирінням залежно від важкості хронічної серцевої недостатності (ХСН). З підвищенням ФК ХСН існує схильність до анемізації, формування ниркової дисфункції та кардіогенного ураження печінки, поширюється систолічна, діастолічна дисфункція ЛШ та легенева гіпертензія. The main links of CHF pathogenesis are: structural-geometric heart reconstruction, myocardium functional state disorder (formation of systolic and diastolic heart functions disorder), local and system inflammatory changes, specific metabolic disorders and so on. The aim of research was the study of changes of laboratory parameters and functional state of the left ventricle (LV) in men with overweight and obesity depending on CHF severity. Methods: There were examined 123 persons with CHF of I-III functional class (FC) who had normal and surplus body weight and abdominal obesity of I-III degree. All patients underwent laboratory and echocardiographic examination. The processing of received data was carried out with methods of parametric and non-parametric statistics. Results: Laboratory changes in men at CHF deepening are demonstrated in inclination to formation and spreading of anemia, kidney dysfunction and cardiogenic liver injury. With an increase of FC of disease there takes place the gradual decrease of CHF frequency with preserved emission fraction (EF) of LV at the expense of systolic dysfunction spreading. The decrease of myocardium systolic function at CHF deepening is attended with development of pulmonary hypertension parallel with spreading and deepening of diastolic dysfunction (DD) of I type. The more severe clinical course of CHF is attended with the decrease of isolated DD frequency of myocardium of I type at the expense of increase of spreading of combined systolic and diastolic dysfunction of the LV. Conclusions: With an increase of CHF FC there takes place an inclination to anemisation, formation of kidney dysfunction and cardiogenic liver injury, the spreading of systolic and diastolic LV dysfunction and pulmonary hypertension.
Changes in laboratory parameters and functional state of the left ventricle in men with overweight and obesity depending on the severity of chronic heart failure
Keywords: серцева недостатність; важкість; чоловіки; ожиріння; лабораторна діагностика; функціональний стан міокарда; heart failure; severity; men; obesity; laboratory diagnostics; myocardium functional state